PENGARUH PELAKSANAAN ANGGARAN DAN PEMAHAMAN REGULASI TERHADAP KETERLAMBATAN PENYERAPAN ANGGARAN PEMERINTAHAN DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Empiris pada Organisasi Perangkat Daerah di Lingkungan Provinsi Riau) - Utama, Muhammad Safera; Basri, Yesi Mutia; Paulus, Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This research aims to determine the effect of budget implementation and understanding ofregulations on delays in regional government budget absorption with organizationalcommitment as a moderating variable. The research method used is a quantitative researchmethod. The population in this research are institutions located in Riau Province. The samplein this study was 150. Data analysis was carried out using classic assumption tests andhypothesis testing using multiple regression methods and moderated regression methods.Based on the research results, it shows that budget implementation and understandingregulations influence budget absorption in Riau Province. Meanwhile, budget implementationand understanding of regulations, which are assisted by the moderating variableorganizational commitment, have no influence on budget absorptionKeywords: Budget Implementation, Understanding Regulations, Delays in RegionalGovernment Budget Absorption and Organizational Commitment